Visualisation of Trajectories of Participation in a Wiki: A Basis for Feedback and Assessment? - Ingvill Rasmussen; Andreas Lund; Ole Smørdal (Universitetsforlaget, 2012)
Learning from digital resources requires different competences compared to learning from textbooks. Such competences cannot be fostered without support; social and material. However, assessment of such practices is not well accounted for. We analyse data from a four year intervention study where teachers and researchers collaborated in developing a wiki to afford relevant tasks and assessment of students' activities. Our findings show that material tools may afford and make visible ideas for future assessment practices, but that such practices have not materialized beyond 'what might be'.